Facile synthesis of organosilica-capped mesoporous silica nanocarriers with selective redox-triggered drug release properties for safe tumor chemotherapy. (20th March 2019) - Shen, Luying; Pan, Shan; Niu, Dechao; He, Jianping; Jia, Xiaobo; Hao, Jina; Gu, Jinlou; Zhao, Wenru; Li, Pei; Li, Yongsheng
Abstract : We develop a facile route to synthesize organosilica-capped mesoporous silica nanocarriers for efficient and safe redox-triggered tumor chemotherapy. Abstract : As drug-delivery carriers for cancer chemotherapy, gatekeeper-capped mesoporous silica nanoparticles (MSNs) have been widely studied due to their high drug-loading capability, controlled drug release property and good biocompatibility. However, the currently reported gatekeeper-capped MSNs suffer from complex synthetic procedures, potential toxicity of gatekeepers, unsatisfactory control on drug stimuli-release, etc . In this work, we develop a simple but efficient approach to fabricate PEGylated organosilica-capped mesoporous silica nanoparticles (POMSNs) by employing a disulfide-doped organosilica coating as the gatekeeper formed by the hydrolysis and condensation of a silane coupling agent 3-(mercaptopropyl)trimethoxysilane (MPTMS) to block the mesopores of MSNs. Owing to the glutathione (GSH)-responsive biodegradation behavior of the disulfide-doped organosilica gatekeeper, the DOX-loaded POMSNs exhibit only 20% cell viability towards SMMC-7721 tumor cells, and almost no toxicity towards L-02 cells at a DOX concentration of 50 μg mL −1 was measured, demonstrating their selective cytotoxicity in vitro . More importantly, it is demonstrated that the DOX-loaded POMSNs exhibit a tumor inhibition rate of 71.3% and negligible systematic toxicity. Consequently, the resultant POMSNs show great potential as drug nanocarriers for redox-responsive drug release and passive-targeting tumor chemotherapy.